PENINGKATAN LITERASI ENERGI TERBARUKAN MELALUI IMPLEMENTASI MICROGRID PANEL SURYA DAN PENGEMBANGAN PLATFORM E-LEARNING DI SMKN 3 TONDANO - Mahendra, I Gede Budi; Wigena, Ida Bagus Weda; Tinambunan, Medi Hermanto (Jurnal Abdi Insani, 2025)
The need for renewable energy literacy in vocational education is becoming increasingly urgent to support energy transition and green education. SMK Negeri 3 Tondano has the potential to develop solar energy through learning activities and electrical engineering practices. However, teachers' and students' understanding of renewable energy concepts, energy efficiency, and solar power generation systems (PLTS) is still limited. This situation has led to low adoption of clean energy technology in teaching and learning processes and the school environment. This community service programme aims to enhance renewable energy literacy and technical capacity among school staff through an educational, participatory, and applied approach. The activities included interactive outreach, technical training, development of a Learning Management System, formation of an Energy Task Force, installation of a 300 Wp microgrid PLTS, and development of technical SOPs. A total of 43 participants, consisting of teachers, students, and technicians, were actively involved. Pre-test–post-test evaluation results showed significant improvements: the average teacher score increased from 58–65 to 84–88, while students improved from 44–52 to 73–79, with an N-Gain of 0.56–0.66. The PLTS system generates 1.2–1.4 kWh per day and can operate practical loads for 3–5 hours. Follow-up activities include integrating renewable energy materials into project-based learning, self-managed LMS management, and the implementation of maintenance SOPs. This activity demonstrates that the school-based energy education model can be replicated to strengthen the energy transition at the national level.